1993
DOI: 10.1093/ndt/8.8.725
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up study of 268 diabetic patients undergoing haemodialysis, with special attention to visual acuity and heterogeneity

Abstract: We studied the long-term outcome of 268 patients suffering from diabetic end-stage renal disease (DM-ESRD) treated with long-term haemodialysis between 1978 and 1991, with special emphasis on visual acuity as well as the heterogeneity of DM-ESRD. The 50% patient survival on haemodialysis was 60 months. Visual disturbances were found in 73.1% (392/536) of eyes at the start of haemodialysis. Chronological assessment of visual acuity demonstrated the stabilization of visual acuity and 87.1% (364/418) of eyes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…It has been observed that after renal transplantation or initiation of dialysis, visual function stabilizes (28). The stabilization could also be due to other factors, such as lower blood pressure during renal replacement therapy (29). A strong positive association between the severity of retinopathy and the severity of nephropathy was noted in this study (r ϭ 0.63, P Ͻ 0.001), which supports the hypothesis that there are common predisposing factors behind these two microvascular complications.…”
Section: Discussionsupporting
confidence: 84%
“…It has been observed that after renal transplantation or initiation of dialysis, visual function stabilizes (28). The stabilization could also be due to other factors, such as lower blood pressure during renal replacement therapy (29). A strong positive association between the severity of retinopathy and the severity of nephropathy was noted in this study (r ϭ 0.63, P Ͻ 0.001), which supports the hypothesis that there are common predisposing factors behind these two microvascular complications.…”
Section: Discussionsupporting
confidence: 84%
“…In several studies, the effect of HD on diabetic retinopathy with or without macular edema was evaluated by fluorescein angiography or ophthalmoscopy [2,3,12,13,14,15,16]. All these studies refer to the effect of HD only on the leakage of diabetic macular edema, as angiography cannot detect retinal thickness changes.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 73.1% of eyes already had visual disturbance and 11% were blind at the time of dialysis initiation 31. Historically, HD has been associated with the stabilisation of retinopathy (87.1% of eye visual acuity stable over at least 2 years follow-up) 31.…”
Section: What Effect Does Diabetes Have On Mortality and Morbidity Inmentioning
confidence: 99%